Assessment of high dilutions on soil microbial respiration - Domingues, Sérgio; Boff, Pedro; Carissimi Boff, Mari Inês (Revista Mexicana de Ciencias Agrícolas, 2025)
Soil health and fertility determine its potential to support crop productive capacity. Organic matter is considered an indicator of biostructure and maintenance of life in the soil. Its role is reflected in microbial activity that can be measured by evaluating CO2 released as a function of metabolic oxidation activities. Microbial respiration, which is more sensitive than physicochemical indicators, provides information on other disturbances. Therefore, the soil microbiota has a high potential to respond to subtle interventions with the application of dynamized high dilutions (homeopathies). Dynamized high dilutions have significantly impacted living things and plant cultivation. This study assessed variations in microbial respiration following the application of these dilutions in Fraiburgo, SC, Brazil, in 2020. Four treatments were used in the laboratory experiments: distilled water (i), 30% alcohol (ii), Calcarea carbonica 30CH (iii) and Silicea terra 30CH (iv), in 10 replications formed by two independent soil samples. The treatments were applied with a manual sprayer in a ratio of 1:99 of water in three different seasons in the soil. The results showed a significant increase in the rates of CO2 released by the soil due to the application of high dilutions by the Anova test, p< 0.05, especially in the first 48 h. The study showed that dynamized dilutions alter the respiratory dynamics of soil microorganisms.